Creative assessment approaches to human interactions and music interfaces technology. A Systematic Literature Review - Pascual-Vallejo, César Daniel; Casillas-Martín, Sonia; Cabezas-González, Marcos (Revista Electrónica Complutense de Investigación en Educación Musical - RECIEM, 2022)
This article reviews the state of the art about previous studies which have evaluated interactions between humans and audio music technologies thus far. The objective is to study how many studies have evaluated singular proactive, creative and expressive interaction of technology users. Also included are studies that integrate aspects related to education, health and well-being, to promote a future enrichment of collaborative work among specialized professionals within the designs of creative music technology, and educational teams in which these types of technological interactions are used. The fourth industrial revolution is progressively hypernormalizing creativity, maintaining a false and excesive social normalization of its functional logic. Its techno-symbolic paradigm affects science, education and the use and appropriation of technology. As a consequence, standardization rigidity and automation normalize creative learning processes, generating cognitive dissonance which affect people’s health and well-being. This reveals the need to find technology designed to be flexible in humans. This study points to the value of practicing music as one of the most revolutionary creative areas in the field of technological cognitive interactions. Through a mixed methodology, based on collecting, analyzing and interpreting most of the relevant sources in the field, and summarized in three main scientific databases, a small percentage of researchers demonstrate a link to the main objective of this previously described study. The conclusions show that the scientific community has not focused on the search for inclusive paradigms that integrate a dimension of evaluation which respects the creative capacities of the technological user, based on an open and holistic concept of education, health and well-being. This indicates the opportunity to implement evaluations through music therapists and artistic-creative therapists within the design processes of creative and expressive technology. This would facilitate a critical and proactive search for new, more respectful, flexible technological paradigms. It would also be resilient for education, health and well-being, including frameworks capable of providing viable alternatives to the problem posed by current technological hypernormalization.